Handbook of hydraulic fracturing - Speight, James G. (John Wiley & Sons, Inc., 2016)
Presents an up-to-date description of current and new hydraulic fracturing processes -Details Emerging Technologies such as Fracture Treatment Design, Open Hole Fracturing, Screenless Completions, Sand Control, Fracturing Completions and Productivity -Covers Environmental Impact issues including Geological Disturbance; Chemicals used in Fracturing; General Chemicals; Toxic Chemicals; and Air, Water, Land, and Health impacts -Provides many process diagrams as well as tables of feedstocks and their respective products.